Natural levels of fungal infections in grasshoppers in northern Benin - Shah, P.; Godonou, I.; Gbongboui, C.; Lomer, C. (Informa UK Limited, 1994)
The infection of grasshoppers by naturally occurring, entomopathogenic fungi was monitored at two sites in Malanville, northern Benin, Africa. Grasshoppers were collected and recorded from the sites between June and December 1992 and all of them, barring the first instars, were incubated in ventilated cages. At the first site, 1343 individuals of 35 grasshopper species were incubated, and at the second site, 857 individuals of 36 grasshopper species were incubated. Three hyphomycete fungi (Deuteromycotina: Hyphomycetes), Metarhizium flavoviride Gams and Rozsypal, Beauveria bassiana (Bals.) Vuillemin and Sorosporella sp. were found infecting grasshoppers. The average incidence of M. flavoviride infection was 2.9% and 1.8% at the two sites for all host species. M. flavoviride sporulated on most grasshopper cadavers within 10 days of collection. B. bassiana and Sorosporella sp. were only collected from one and five grasshopper individuals respectively. A significant difference was noted in the time to death of small grasshopper species infected with M. flavoviride compared to larger species. At one site, M. flavoviride infection was positively correlated with rainfall during the 10‐day period in which samples were taken.